2023
DOI: 10.1111/ahe.12922
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ADAMTS 1‐4‐8 and placental growth factor in ovary and oviduct during pregnancy in the first trimester

Abstract: A Disintegrin and Metalloprotease Domains with Thrombospondins Motifs (ADAMTS), proteinases responsible for the destruction of extracellular matrix structures, have essential roles in the physiological and pathological processes of the female reproductive system, which is a dynamic structure. This study aimed to evaluate the immunoreactivity of placental growth factor (PLGF) and ADAMTS' (1, -4, and -8) in the ovary and oviduct during pregnancy in the first trimester. Our findings suggest a predominant role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In ovaries, we observed up-regulation of genes related to the process of ovulation, corpus luteum formation, and implantation of the embryo, as indicated by adamts [49] and vcan [50].…”
Section: Genes Enrichedmentioning
confidence: 87%
“…In ovaries, we observed up-regulation of genes related to the process of ovulation, corpus luteum formation, and implantation of the embryo, as indicated by adamts [49] and vcan [50].…”
Section: Genes Enrichedmentioning
confidence: 87%
“…Previous research has shown that several ADAMTS proteins are expressed in human, mouse, and rat ovary, oviduct, placental and uterine tissues (Feng et al, 2021;Mani et al, 2019;Park et al, 2021;Qu & Khalil, 2022;Tatar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown Namli Kalem et al, 2017). ADAMTS-1 may create a pregnancysupportive uterine environment by controlling the breakdown of the decidual ECM and the substantial vascular remodelling that occurs during implantation and placentation (Lee et al, 2014;Tatar et al, 2023). According to a sheep study, ADAMTS-1 is also responsible for forming new blood vessels that provide nutrients to the placenta and endometrium (Dunlap et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The prepared sections were photographed under a light microscope (Zeiss, Axiolab) with a camera attachment. Staining intensities were evaluated as (-); no staining, (-/+); partial staining, (+); weak staining, (++); moderate staining, (+++); strong staining (Tatar et al, 2023;Tufekci et al, 2023).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Ten randomly selected regions in brain tissue sections from each rat were graded semi-quantitatively using an objective magnification of 40X. The median H-score value was used to classify each region's expression level as either low or high (Numata et al, 2013;Tatar et al, 2023).…”
Section: Semi-quantitative Analysismentioning
confidence: 99%